Extraction of fish collagen using enzymatic process - Jaswir, Irwandi; Hazahari, Noor Yuslida; Mirghani, Mohamed Elwathig Saeed (IIUM Press, 2011)
Gelatin is a high molecular weight polypeptide obtained by partial hydrolysis of II Willer insoluble fibrous prolein collagen. Collagen is thc primary protein component of mammalian and fish skins, bones and conneclive tissues. Tilt properties of gelatin including viscosity, gel slrength. gelling and melting temperafUre will affect lhe quality of gelalin produced. The type of chemical pre-treatment and pa]1lm~'lers of extraction can as well influence the length of polypeptide chains and thc functional properties of the gelatin. The thermal shrinkage, dcnaluration temperature of collagen and melting temperature of gelatins derived from different sources of fish will gteatly differ and to some extem limit the application of fish gelatins as compared to mammalian gelatins. With regard to this, the study was earned out to optimize gelatin extraction from four types of local fish: 'lenahak' (Lu/ianus agenlimawlarus), 'Kerapu' (Epinephelus sex/uscia/as). 'Kerisi' (Prislipomadt's I)pu.\) and 'Kembong' (RaSlrelliger kanagllrla) so as to seareh for a possibility of shortening the time of extraction and to modify the propmies of fish gelatins with the aid of an enlyme: lransglutaminase, in order to delennine optimum conditions of enzymatic cross-linking of fish gelatins so that the gel could be obtained at room temperature. The physicochemical characteristics (appearance and odour) including amino acid compositions of each type or fish was also dctennined. Comparisons of spectra between gelatins of different sources: !lsh. pork and commercial, were camed out using the FTIR speCtroscopy and the differences and similarities 10 functional groups present were recognized_ The results show lhal by using very small. cuI. fish skins, significantly shonens the time or extraction in comparison ",itlt extraction methods where whole skins arc used. Modific3lion or fish gelatins with transglutaminase were also possihle if proper enz}me and substmte concentration are being used.